2023
DOI: 10.1136/bmjgh-2022-009693
|View full text |Cite
|
Sign up to set email alerts
|

Impact of breastfeeding on the incidence and severity of respiratory syncytial virus (RSV)-associated acute lower respiratory infections in infants: a systematic review highlighting the global relevance of primary prevention

Abstract: BackgroundRespiratory syncytial virus (RSV) is the principal cause of acute lower respiratory infections (ALRI) among infants worldwide, and an important cause of morbidity, hospitalisation and mortality. While infants are universally exposed to RSV, most mortality occurs among normal term infants from low-income and middle-income countries. Breastfeeding has been suggested to have a protective effect against RSV infection. This study aims to determine the association of breastfeeding on the frequency and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 68 publications
2
12
0
Order By: Relevance
“…There were over 3600 cases of RSV reported in Ireland in winter 2018/2019, which was the highest number of notifications recorded before COVID‐19 pandemic, since RSV became a notifiable illness in Ireland in 2012 16 . While during the COVID‐19 pandemic and lockdowns RSV infection declined drastically, there has been a resurgence with even higher RSV rates once the stringent public health mitigation measures against COVID‐19 were discontinued 17,18 . Globally, in 2019, 33 million episodes of RSV‐associated ALRI, 3.6 million RSV‐associated hospital admissions, 26 300 RSV‐associated ALRI related in‐hospital deaths, and 101,400 RSV‐attributable overall deaths occurred in infants and children aged 0–60 months, with almost half of these occurring in infants under 6 months 19 .…”
Section: Introductionmentioning
confidence: 99%
“…There were over 3600 cases of RSV reported in Ireland in winter 2018/2019, which was the highest number of notifications recorded before COVID‐19 pandemic, since RSV became a notifiable illness in Ireland in 2012 16 . While during the COVID‐19 pandemic and lockdowns RSV infection declined drastically, there has been a resurgence with even higher RSV rates once the stringent public health mitigation measures against COVID‐19 were discontinued 17,18 . Globally, in 2019, 33 million episodes of RSV‐associated ALRI, 3.6 million RSV‐associated hospital admissions, 26 300 RSV‐associated ALRI related in‐hospital deaths, and 101,400 RSV‐attributable overall deaths occurred in infants and children aged 0–60 months, with almost half of these occurring in infants under 6 months 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Although nirsevimab and palivizumab have acceptable effectiveness, these monoclonal antibodies are expensive and mostly available to high-income countries [ [19] , [20] , [21] ]. In contrast, breastfeeding, a universal primary prevention strategy to reduce infectious diseases in infants, consistently confers benefits against both the incidence and severity of RSV bronchiolitis in infants [ 22 ]. A systematic review of 19 studies comprising 16,787 infants from 31 countries concluded that not being breastfed poses a significant risk of severe RSV disease and hospitalization [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, breastfeeding, a universal primary prevention strategy to reduce infectious diseases in infants, consistently confers benefits against both the incidence and severity of RSV bronchiolitis in infants [ 22 ]. A systematic review of 19 studies comprising 16,787 infants from 31 countries concluded that not being breastfed poses a significant risk of severe RSV disease and hospitalization [ 22 ]. Conversely, exclusive breastfeeding for 4–6 mo significantly reduces hospitalization, length of stay, supplemental oxygen therapy, and admission to intensive care units [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is a recognized fact that breastfeeding contributes to children's cardiovascular and respiratory health in the short, medium, and long term. Regarding the respiratory tract, a 2018 meta-analysis reported that donor milk protects against bronchopulmonary dysplasia [1]; former and current research has found that infants who were breastfed had subsequently fewer lower tract respiratory hospitalizations than formula-fed infants [2]; a systematic review that summarizes the research on the link between breastfeeding and bronchiolitis from 2000 to 2021 shows that both exclusive and partial breastfeeding lower the severity of bronchiolitis [3]; and a 2021 meta-analysis restricted to cohort or randomized studies found that both any breastfeeding and exclusive breastfeeding are linked to a lower risk of getting childhood asthma [4]. In addition, emerging research suggests that more prolonged breastfeeding benefits lung function in later childhood, with the most consistent effect on increased lung growth and vital capacity [5].…”
Section: Introductionmentioning
confidence: 99%